Stem Cell Differentiation Stage Factors (SCDSFs) Taken from Zebrafish Embryo during Organogenesis and their Role as Epigenetics Regulators able to Reverse Neurosensory Hearing Loss - Mario Biava Pier; Ciaurelli Stefano; Benzi Cipelli Riccardo; Pisano Gianpaolo (Journal of Otolaryngology Advances, 2022)
This translational paper discusses differentiation‑stage factors from zebrafish embryos as epigenetic regulators with potential to reverse neurosensory hearing loss. It outlines experimental evidence, delivery concepts, and research gaps.
Keywords: Stem Cell